A fast and facile platform for fabricating phase-change materials-based drug carriers powered by chemical Marangoni effect. (April 2021) - Hsieh, Meng-Hsuan; Wei, Hao-Ji; Chen, Kuan-Hung; Wang, Hung-Chen; Yu, Chia-Hsiang; Lu, Ting-Hsuan; Chang, Yen; Sung, Hsing-Wen
Abstract: Emulsions of oil droplets as drug carriers are typically formulated by emulsification, which is complex and time-consuming and requires high energy input. To address these concerns, a fast and facile method for fabricating lipid-based oil droplets, using propulsive forces that arise from the chemical Marangoni effect, is developed for the oral delivery of lipophilic drugs, such as vitamin D. The oil droplets are prepared by solubilizing vitamin D in a phase-changeable fatty acid with the addition of ethanol as an oil phase, which is then deposited on a water bath. As a result of the differing surface tensions of water and ethanol (chemical energy), propulsive Marangoni forces are generated (kinetic energy), rapidly spreading the oil phase into many tiny oil droplets. To prevent their coalescence, the generated oil droplets are solidified by reducing their environmental temperature. Following oral administration, the fluidity of the solidified droplets increases at body temperature; they can be further emulsified into the vitamin D-containing micelles by intestinal bile salts. The micelles are then taken up by the intestinal epithelial cells, enabling their contained vitamin D to be absorbed into systemic circulation, improving its oral bioavailability.